In situ SAXS study of fractal structure of non-caking coal during carbonisation. (1st February 2021) - Lv, Qi; Li, Zhihong; Liu, Li-Zhi; Zhao, Yixin; Li, Dongfeng; Guo, Wenyan; Mo, Guang; Lv, Baoliang
ABSTRACT: The changes in fractal structure during high-temperature (1200°C) carbonisation of a Chinese non-caking coal were studied in situ by synchrotron radiation small-angle X-ray scattering (SAXS). The results indicate that the raw coal, char and carbon residue possess a surface fractal structure, and a change in fractal dimension during carbonisation indicates that the process exhibits different stages. Changes in the fractal dimension and the various mechanisms during carbonisation are revealed and analysed.